2011
DOI: 10.1002/oa.1269
|View full text |Cite
|
Sign up to set email alerts
|

Boards and Cords: Discriminating Types of Artificial Cranial Deformation in Prehispanic South Central Andean Populations

Abstract: For over a century, a number of ambiguous typologies have been employed to distinctly categorise types of artificial cranial deformation. This paper provides a quantitative method, based on multiple dimensions and discriminant function analysis, by which to assign skulls not only into discrete categories: deformed or not, but also by type: annular or tabular. A series of prehispanic, adult, human crania (n=469) from archaeological sites in Argentina, Bolivia, Chile and Peru represented by both normal and artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Our results correspond with previous studies (Antón, 1989;Kohn et al, 1993;O'Brien and Stanley, 2013) that reported shorter cranial length and broader cranial breadth in the anteroposterior cranial modification group than in the normal group. In this regard, the two deformed crania from Yean-ri in this study can be allocated to the anteroposterior cranial modification type based on the flatter frontal and occipital bones and superoposteriorly developed parietal bones.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results correspond with previous studies (Antón, 1989;Kohn et al, 1993;O'Brien and Stanley, 2013) that reported shorter cranial length and broader cranial breadth in the anteroposterior cranial modification group than in the normal group. In this regard, the two deformed crania from Yean-ri in this study can be allocated to the anteroposterior cranial modification type based on the flatter frontal and occipital bones and superoposteriorly developed parietal bones.…”
Section: Discussionsupporting
confidence: 83%
“…Artificial cranial deformation has been considered 'nature's experiment,' allowing the examination of the association of cranial parts and cranial development by dividing the cranium into vault, face, and basicranium (Antón, 1989;Cheverud et al, 1992;Meiklejohn et al, 1992;Kohn et al, 1993;Lieberman, 2011;O'Brien and Stanley, 2013). It was hypothesized that vault modification affected both the basicranium and the face as they share several functions such as accommodation and protection of the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practitioners of cranial vault modification intentionally reshape the head using binding fabrics and/or stiff pads during the first years of life, when the bones of the skull are malleable (Blom 2005;O'Brien and Stanley 2013;Tiesler 2014;Torres-Rouff 2008). Cranial modification is an ascribed symbol of group identity and a permanent signifier of social identity imposed upon children; it reflects a decision made by community members and likely represents Wiessner's (1983) emblemic style.…”
Section: Community Identities Through Cranial Vault Modificationmentioning
confidence: 99%
“…Other studies address the issue of classification of artificially modified cranial forms by using linear measurements, as well as indices and angles, to reliably evaluate cases of ACM (e.g., Clark et al, ; Falkenburger, ; O'Brien & Stanley, ; Pomeroy, Stock, Zakrzewski, & Lahr, ; Romano, , ). Although combinations of these metric traits allow for the identification of major ACM forms to a certain extent (e.g., Falkenburger, ; O'Brien & Stanley, ), the limited number of recordable variables on the cranial vault prevents clear discrimination among certain types and is inadequate for accurately describing fine shape changes between individuals.…”
Section: Introductionmentioning
confidence: 99%